Pengaruh variasi organic loading rate sampah buah jeruk terhadap produksi biohidrogen pada reaktor kontinu - Baruna Sakti Wicaksono Bonanza; Sarto Sarto (Jurnal Rekayasa Proses, 2016)
Biohydrogen is a potential alternative energy generated through the process of dark fermentation of organic waste. This research aims to determine the effect of organic loading rate (OLR) variations of orange waste on biohydrogen production. This research dealt with the production of biohydrogen in the continuous system. The reactor was equipped with circulation and operated anaerobically. The inoculum was taken from the sludge of the biogas installation in Gemah Ripah Fruit Market. Orange waste was used in three variations of organic loading rate (OLR) at 2.2, 2.5, and 3.1 L/day. The results revealed that the daily productions of gas for those OLR are about 15, 35, and 26 L/day respectively. Futhermore, for OLR of 2.5 L/day the total solid decreased from about 8 to 5%.